Hemispheric Contrast of Inorganic Chlorine Partitioning in the Polar Lower Stratosphere during Ozone Recovery Period Observed from Space - 林田, 佐智子; 杉田, 考史 (SOLA)
The time evolution of two major chlorine reservoirs, HCl and ClONO2, in the polar lower stratosphere for both hemispheres in late spring and early summer was analyzed by utilizing satellite measurements. Analysis of the collocated ClONO2 observed with ILAS, and HCl observed with HALOE indicated that Cly was mostly in the form of HCl in the Antarctic vortex in November 1996, while more than half was ClONO2 in the Arctic vortex in March 1997. The analysis of N2O indicates that there was strong subsidence of the air inside the Antarctic vortex. The vortex remnant with HCl-rich air persisted in December 1996 even after the vortex weakened, suggesting slow mixing in the boundary. The ClONO2/Cly ratio was about 0.3, which was derived from analysis of correlation with N2O, as a representative value for the extravortex air and upper air inside the vortex (with potential temperature greater than ∼600 K) in both hemispheres in spring. https://www.jstage.jst.go.jp/article/sola/3/0/3_0_117/_article